Application of an Integrated and Open Source Workflow for LC-HRMS Plant Metabolomics Studies. Case-Control Study: Metabolic Changes of Maize in Response to Fusarium verticillioides Infection - Ciasca, Biancamaria; Lanubile, Alessandra; Marocco, Adriano; Pascale, Michelangelo; Logrieco, Antonio F.; Lattanzio, Veronica M. T. (Frontiers in Plant Science, 2020)
Liquid chromatography coupled with high resolution mass spectrometry (LC-HRMS) represents the most powerful metabolomics platform to investigate biological systems. Reproducible and standardized workflows allow to obtain a meaningful biological interpretation. The purpose of this study was to set up and apply an open source workflow for LC-HRMS metabolomics studies. Key steps of the proposed workflow were: (1) experimental design, (2) sample preparation, (3) LC-HRMS analysis, (4) data processing, (5) custom database search, (6) statistical analysis, (7) compound identification and (8) biochemical interpretation. Its applicability was evaluated through the study of metabolomics changes of two maize recombinant inbred lines (RIL) with contrasting phenotypes with respect to disease severity after F. verticillioides infection of seedlings. Analysis of data from the case study revealed abundance change in metabolites belonging to different metabolic pathways, including two amino acids (L-tryptophan and tyrosine), three N-hydroxynnamic acid amides (HCAAs) and four flavonoids.